Determination of Residual Urine with 99mTc-DTPA - Kempi, V.; van der Linden, W. (Nuklearmedizin - NuclearMedicine, 1974)
Residual urine was determined with a new technique using 99mTc-DTPA. In contrast to the 131I labelled substances now in use this compound allows for visualization of the bladder with a short measuring time, satisfactory counting statistics and low radiation dose. No blocking of the thyroid gland is necessary. In 26 consecutive patients the residual urine was determined with this method and by catheterization. The correlation between these two measurements was very high.